MARKETING STRATEGIES TO INCREASE FISH SALES AT UD. UDIN JAYA IN MATTIRO BAJI VILLAGE, KEPULAUAN TANAKEKE DISTRICT, TAKALAR REGENCY - Sri Wahyuni; Marhawati Najib, Muhammad Rakib, Agus Syam, Asmayanti (CV. ADIBA AISHA AMIRA, 2024)
This research aims to analyze the appropriate marketing strategies to increase fish sales at UD. Udin Jaya. The study employs a qualitative method with a case study approach using SWOT analysis. Data were obtained through interviews with the owner of UD. Udin Jaya, employees, and customers. The results indicate that UD. Udin Jaya has a focus that allows the company to leverage its strengths and opportunities, thereby generating various strategies to enhance sales at UD. Udin Jaya.